Mulheres & sistema prisional: o sentido do trabalho para quem viveu e vive sob a égide do cárcere - Bitencourt, álvaro Hummes (2012)
Brazil, the last twelve years, has been making the consolidation of data that illustrate a new logic within the context of the nation's prison reality. Such an avid statistics elucidate growth of women involved in crime and, consequently, with the jail. According to the National Penitentiary Department of the Ministry of Justice, Depen / MJ, the growth rate of the Brazilian women's prison in the first ten years of the past decade was 252%, whereas the increase in men's prison system was estimated at 115%. Thus, we can see that while the male population has doubled, the female more than tripled. Within this context, the scope of the search that follows results from field work conducted from April 2010 to August 2012, the female prison Madre Pelletier and the Foundation of the Egress of Prisons, the FAESP - both located in Porto Alegre, Rio Grande do Sul this period, there were semi-structured interviews with six women, three of preys Madre Pelletier and three discharged inmates met by Faesp. The objective of the study is to know how the work experiences are integrated into life trajectories of trapped and discharged the prison system, according to the narratives of the interviewees themselves. Finally, we emphasize that the purpose of this research is also looking to expand, complement and enhance the knowledge of the female prison of cyclical framework established in Brazil, as well as provide new elements to help support future formulations of public policy on the issue.